2000
DOI: 10.4049/jimmunol.165.11.6322
|View full text |Cite
|
Sign up to set email alerts
|

The VλJλ Repertoire in Human Fetal Spleen: Evidence for Positive Selection and Extensive Receptor Editing

Abstract: VλJλ rearrangements obtained from genomic DNA of individual IgM+ B cells from human fetal spleen were analyzed. A nonrandom pattern of λ gene rearrangements that differed from the adult Vλ repertoire was found. The Vλ distal genes 8A and 4B were absent from the nonproductive fetal repertoire, whereas 2E and 3L were overrepresented and 1B was underrepresented in the productive fetal repertoire. Positive selection of the Vλ gene, 2E, along with Vλ rearrangements employing homologous VλJλ joins were observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
2
19
1
Order By: Relevance
“…In the present analysis, a low frequency of microhomologies was observed. Notably, the frequency of microhomologies seems to be less than that found in fetal (49) or neonatal (25) arrangements.…”
Section: Discussionmentioning
confidence: 91%
“…In the present analysis, a low frequency of microhomologies was observed. Notably, the frequency of microhomologies seems to be less than that found in fetal (49) or neonatal (25) arrangements.…”
Section: Discussionmentioning
confidence: 91%
“…Decreased restriction during fetal life also occurs in sheep, in which there is no bias for IGHJ selection in fetal or neonatal stages but IGHJ1 is most frequently used in the adult (Gontier et al 2005). In contrast, humans (Lee et al 2000) and swine (Butler et al 2013; Wertz et al 2013) have restricted IGLV utilization in their pre-immune Ig repertoires. It remains unknown what governs the shift to a predominance of IGLV8-128 and IGLJ7 in the adult horse.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the prognosis of severe rheumatoid arthritis (RA) patients has improved owing to the development of biological disease modifying antirheumatic drugs (DMARDs) such as tumour necrosis factor (TNF) inhibitors (antitumour necrosis factor (aTNF)) 13. However, growing experience with aTNF has also demonstrated that these drugs are often not the final step in RA treatment.…”
Section: Introductionmentioning
confidence: 99%